Actitudes en la conservación del ambiente en alumnos del Instituto Superior Tecnológico Fernando Lores Tenazoa de Tamshiyacu (especialidad agropecuaria). distrito de Fernando Lores. Loreto. 2021 - Navarro Pereyra, Yolanda Brannigan (2022)
This research is entitled Attitudes in the conservation of the environment in students of the Instituto Superior Tecnológico Fernando Lores Tenazoa de Tamshiyacu (agricultural specialty). District of Fernando Lores. Loretto. 2021. Having as objectives, to describe the attitudes in the conservation of the environment, of the students of the IST Fernando Lores Tenazoa of the city of Tamshiyacu, (agricultural specialty), district of Fernando Lores in its three dimensions, cognitive, affective and reactive. The non-experimental, quantitative, cross-sectional research design was used. With a simple probabilistic sample, where 71 students enrolled in the school year participated. The results obtained from the surveys were demonstrated through descriptive statistics. From the work it is established that the attitudes in the conservation of the environment, by the students of the Instituto Superior Tecnológico Fernando Lores Tenazoa de Tamshiyacu, have high values, of the dimensions evaluated: cognitive (64.79%), affective (47.88%) and reactive (83.10%). In the affective dimension, values of attitudes towards the conservation of the environment of average attitudes (22.53%) and low (12.68%) were found. In the affective dimension, mean percentage values of the level of attitudes towards the conservation of the environment are recorded. (9.86%) and low-level attitudes (12.68%). In the reactive dimension in levels of medium attitude towards the conservation of the environment we have (5.63%) and low-level attitudes (11.27%). It is concluded that the environmental awareness of the students of the IST Fernando Lores de Tamshiyacu is high, where it is taken into account that one of the most powerful factors when an attitude is created or influenced is the direct experience that the individual has with the environment. attitude object.